The association between study characteristics and outcome in the relation between job stress and cardiovascular disease – a multilevel meta-regression analysis - Szerencsi, Karolina; van Amelsvoort, Ludovic GPM; Viechtbauer, Wolfgang; Mohren, Danielle CL; Prins, Martin H.; Kant, IJmert (Scandinavian Journal of Work, Environment & Health, 2012)
' ' OBJECTIVES ': 'Studies about job strain and cardiovascular disease (CVD) have yielded inconsistent results, which hinders making a firm conclusion about the association. Inconsistent findings may be the result of methodological differences. If the relative CVD risk is influenced by methodological differences, these differences should be explored in more detail in future research to clarify which methodological characteristics are inherent to obtain the most accurate estimate between job strain and CVD risk. By assessing how study characteristics are associated with the outcome, we take the first step in unraveling this association. In this review, we explore the following research question: are study characteristics associated with the size of the reported relative CVD risk? ' ' METHODS ': 'A systematic literature search yielded 71 studies about job stress, assessed with the demand–control model, and CVD. Traditional meta-regression was extended enabling the use of correlated data to quantify heterogeneity within and between studies. ' ' RESULTS ': 'Compared to studies that use the original Job Content Questionnaire (JCQ), studies in which a more deviant form of the JCQ was used yielded, on average, 43% higher estimates. Studies conducted in the USA yielded about 26% lower estimates compared to studies conducted in Scandinavian countries. ' ' CONCLUSIONS ': 'Several study characteristics are associated with the size of the reported relative CVD risk. Many of these study features are related to the validity of the exposure and outcome assessment and are inherent to obtain an accurate estimate between work stress and CVD risk. More research is needed to clarify why these study features impact the average relative CVD risk.
Keywords: cardiovascular disease; coronary heart disease; decision latitude; heterogeneity; job demand; job strain; job stress; meta-analysis; meta-regression analysis; multilevel meta-regression analysis; psychosocial factor; review; stroke; study characteristic; systematic review; work stress